Sosialisasi Kreasi Pangan Lokal “AKANG” (Kelakai dan Ikan Saluang) sebagai Cemilan pada Penderita Diabetes: Socialization of Local Food Creations "AKANG" (Kelakai and Saluang Fish) as Snacks for Individuals with Diabetes - Yuliani, Ni Nyoman Sri; Ahmad, Farah Fauziyah Radhiyatulqalbi; Turnip, Oktaviani Naulita; Hanasia, Hanasia; Komara, Nisa Kartika; Agustira, Dewanti; Sayyidinoor, Muhammad Alif; Sadek, Yitro Tuah HR; Safitri, Andini; Mudatama, Yusuf; Efendy, Dennisya Azzahra; Upel, Dean Antoni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Training on the Use of Learning Management Systems (LMS) is essential for enhancing the quality of academic services in an era of increasingly adopting technology. Integrating LMS with conventional methods, known as blended learning, which combines distance learning, regular classes, and LMS, results in a more effective and efficient learning process. With the shift towards digital learning, LMS use becomes crucial for improving the efficiency, accessibility, and quality of academic services. Through e-learning, students not only listen to lectures but also actively observe, perform, demonstrate, and more. Teaching materials can be virtualized in various formats to create more engaging and dynamic content, motivating students to delve deeper into the learning process. This training aims to equip educators and administrative staff with LMS features and potential, enabling them to maximize its use for content delivery, facilitating teacher-student interaction, and enhancing course management and evaluation. The training methods include presentations on basic LMS concepts, demonstrations of key features, and hands-on practice sessions that allow participants to actively engage in the learning process. Additionally, interaction between participants and facilitators is enhanced through discussions and Q&A sessions, ensuring deep understanding and practical skills in LMS usage to improve academic service quality. Consequently, this training is expected to provide a solid foundation for educational institutions to meet challenges and leverage the opportunities offered by the digital era in providing quality academic services.